Albmulaččat, ulddat and nubbi áibmu - Mikkel Nils Sara; Lovisa Mienna Sjöberg (Sámi dieđalaš áigečála)
Stories about ulddat, i.e. about inhabitants of another sphere/universe, are well known all over Sápmi. These stories represent a worldview that is mentioned already in the earliest, comprehensive written sources about the Sámis, i.e. from the 17th century. In this article we take a closer look at stories from RidduDuottarMuseat in Guovdageaidnu. The stories about ulddat presume a context that implies among other things the existence of another áibmu, i.e. another sphere or universe not usually seen or heard by us. The second áibmu and the various themes connected to it constitute parts of what people everywhere in Sápmi have explained to be their worldview, belief system, and theoretical starting point. The stories presented in this article give us examples of how albmulaččat, people of our sphere, have experienced ulddat, examples of how these beings appear to us looking like the humans and like the animals in our áibmu. The article discusses how these stories influence our actions and ways of thinking.